Solve by any method:

4x-y+z=-5

2x+2y+3z=10

5x-2y+6z=1

I tried using the method of Gaussian Elimination but I got kinda messed up, I'd appreciate some help. Thanks!

Guest Oct 5, 2020

#1

#5**+1 **

Add 2^{nd} and 3rd

7x + 9z = 11

Multiply 1st by 2 and add to 2nd

10x +5z=0 mutiply red by -10/7 and add to green

-10/7 (9z)+5z = -10/7 (11) solve for z

z = 2

Plug z value into 2nd equation and 3rd equation

2x - 2y = 4 5x -2y = -11 add these two equations

7x = - 7

x = - 1

Now sub in the values of z and x into any of the equations to compute z

2(- 1) + 2y +3(2) = 10

y = 3

Guest Oct 5, 2020